Complexation of Cm(III) with the recombinant N-lobe of human serum transferrin studied by time-resolved laser fluorescence spectroscopy (TRLFS) - Bauer, Nicole; Smith, V. C.; MacGillivray, R. T. A.; Panak, Petra (Dalton transactions, 2015)
The complexation of Cm(III) with the recombinant N-lobe of human serum transferrin (hTf/2N) is investigated in the pH range from 4.0 to 11.0 using TRLFS. At pH ≥ 7.4 a Cm(III) hTf/2N species is formed with Cm(III) bound at the Fe(III) binding site. The results are compared with Cm(III) transferrin interaction at the C-lobe and indicate the similarity of the coordination environment of the C- and N-terminal binding sites with four amino acid residues of the protein, two H2O molecules and three additional ligands (e.g. synergistic anions such as carbonate) in the first coordination sphere. Measurements at c(carbonate)tot = 0.23 mM (ambient carbonate concentration) and c(carbonate)tot = 25 mM (physiological carbonate concentration) show that an increase of the total carbonate concentration suppresses the formation of the Cm(III) hTf/2N species significantly. Additionally, the three Cm(III) carbonate species Cm(CO3)+, Cm(CO3)2− and Cm(CO3)33− are formed successively with increasing pH. In general, carbonate complexation is a competing reaction for both Cm(III) complexation with transferrin and hTf/2N but the effect is significantly higher for the half molecule. At c(carbonate)tot = 0.23 mM the complexation of Cm(III) with transferrin and hTf/2N starts at pH ≥ 7.4. At physiological carbonate concentration the Cm(III) transferrin species II forms at pH ≥ 7.0 whereas the Cm(III) hTf/2N species is not formed until pH > 10.0. Hence, our results reveal significant differences in the complexation behavior of the C-terminal site of transferrin and the recombinant N-lobe (hTf/2N) towards trivalent actinides.